UPLC-MS/MS Profile Combined With RNA-Seq Reveals the Amino Acid Metabolism in Zanthoxylum bungeanum Leaves Under Drought Stress - Hu, Haichao; Fei, Xitong; He, Beibei; Chen, Xin; Ma, Lei; Han, Peilin; Luo, Yingli; Liu, Yonghong; Wei, Anzhi (Frontiers in Nutrition, 2022)
Zanthoxylum bungeanum leaves have a unique taste and incomparable nutritional value and hence are popular as a food item and traditional medicine in China. However, the studies on the metabolites in Z. bungeanum leaves are quite limited, especially for amino acids. Therefore, this study explored the amino acid component in Z. bungeanum leaves and also the accumulation mechanism under drought stress in two Z. bungeanum cultivars using the widely targeted metabolome combined with transcriptome analysis. A total of 56 amino acids and their derivatives were identified in Z. bungeanum leaves, including 9 essential amino acids. The total amino acid content with most individual amino acids increased under progressive drought stress. More differentially accumulated amino acids (DAAs) and differentially expressed genes were found in FJ (Z. bungeanum cv. ‘Fengjiao’) and HJ (Z. bungeanum cv. ‘Hanjiao’). The orthogonal projections to latent structures discriminant analysis identified nine and seven indicator DAAs in FJ and HJ leaves, respectively. The weighted gene co-expression network analysis showed that the green module significantly correlated with most indicator DAAs and revealed the important role of FBA3, DELTA-OAT, PROC, and 15 transcription factor genes in regulating the amino acid synthesis. Furthermore, the correlation analysis and redundancy analysis identified four candidate synthesis genes (ASNS, AK, ASPS, and PK) in amino acid biosynthetic pathway. This study provided useful information for the development of Z. bungeanum leaves in food and nutrition industry but also laid the foundations for future molecular breeding.